Modeling Intermittent Running from a Single-visit Field Test - Galbraith, A.; Hopker, J.; Passfield, L. (International Journal of Sports Medicine, 2015)
This study assessed whether the distance-time relationship could be modeled to predict time to exhaustion (TTE) during intermittent running. 13 male distance runners (age: 33±14 years) completed a field test and 3 interval tests on an outdoor 400 m athletic track. Field-tests involved trials over 3 600 m, 2 400 m and 1 200 m with a 30-min rest between each run. Interval tests consisted of: 1 000 m at 107% of CS with 200 m at 95% CS; 600 m at 110% of CS with 200 m at 90% CS; 200 m at 150% of CS with 200 m at 80% CS. Interval sessions were separated by 24 h recovery. Field-test CS and D′ were applied to linear and non-linear models to estimate the point of interval session termination. Actual and predicted TTE using the linear model were not significantly different in the 1 000 m and 600 m trials. Actual TTE was significantly lower (P=0.01) than predicted TTE in the 200 m trial. Typical error was high across the trials (range 334–1 709 s). The mean balance of D′ remaining at interval session termination was significantly lower when estimated from the non-linear model (−21.2 vs. 13.4 m, P<0.01), however no closer to zero than the linear model. Neither the linear or non-linear model could closely predict TTE during intermittent running.
Keywords: critical speed; interval training; modeling performance